Dynamic evaluation and sensitivity analysis of China’s industrial solid waste management efficiency based on ecological environment cycle perspective - Guan, Xin-ge; Ren, Fang-rong; Fan, Gao; Zhang, Qing-qing; Wu, Tao-feng (Frontiers in Environmental Science, 2024)
IntroductionThe recycling and repurposing of industrial solid waste is a crucial element of sustainable development in growing industrialized nations.MethodsAn advanced two-stage Data Envelopment Analysis (DEA) model was employed to assess the effectiveness of solid waste management across all 31 provinces in China throughout the period spanning from 2016 to 2022.ResultsThe research findings suggest the following: (1) The circular economy has shown varying degrees of improvement in efficiency across most regions. (2) The average efficiency of the resource reuse stage is not higher than 0.4, indicating significant room for development that requires serious attention. (3) The western region has a higher average solid waste treatment efficiency of 0.65 compared to 0.53 in the eastern region, while the central region falls at a moderate level. Furthermore, this work employed sensitivity analysis to examine the resilience of regional efficiency research and discovered that the overall findings remain statistically significant. Hence, it is imperative to simultaneously enhance the internal administration of businesses and enhance governmental environmental legislation and regulations, with the aim of attaining the utmost optimization of resource recycling.DiscussionThis paper presents policy suggestions for enhancing the solid waste recycling system within provincial government departments, while also establishing the foundation for the expansion of the solid waste treatment industry, which is necessary to accomplish the goal of “double carbon”.